42‐1: Invited Paper: Bit‐Depth Constrained Black Level for High Dynamic Range Displays. Issue 1 (29th May 2019) - Boitard, Ronan; Ploumis, Stelios; Damberg, Gerwin; Ballestad, Anders
Abstract : High Dynamic Range (HDR) workflows provide increased peak luminance and lower black levels leading to a significantly enhanced quality of experience. HDR pixels also represent more tonal values across the dynamic range by using a higher bit‐depth along with different perceptual transfer functions. However, many light emitting display devices modulate light using a limited bit‐depth in the linear domain. It is thus challenging for such display systems to achieve simultaneously high peak luminance and high amount of information in the shadows. In this paper, we assess the required bit‐depth to accurately reproduce the shadow information of an HDR signal for different display capabilities.